2001
DOI: 10.1046/j.0021-8790.2001.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term study of reproductive performance in tree swallows: the influence of age and senescence on output

Abstract: Summary 1.We describe age-related reproductive performance and recapture rates of tree swallows ( Tachycineta bicolor Vieillot) based on a 25-year study of a nestbox population in southeastern Ontario, Canada (1975-99). 2. Performance improved from first-time breeders to intermediate-aged birds. Nest initiation advanced, and clutch size increased in both sexes. In females the number of hatchlings and fledglings increased, and the proportion of nests failing completely declined. Performance declined in females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 95 publications
7
106
2
1
Order By: Relevance
“…We used a factorial experimental design with one factor being adult female age (young, 1 year; mid-age, 2 and 3 years; old, 4 years and older), following the age categories used by Robertson and Rendell (2001). Only individuals that could be unambiguously classified into these age categories based on their banding history were included in the experiment.…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a factorial experimental design with one factor being adult female age (young, 1 year; mid-age, 2 and 3 years; old, 4 years and older), following the age categories used by Robertson and Rendell (2001). Only individuals that could be unambiguously classified into these age categories based on their banding history were included in the experiment.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Tree Swallows are small (;20 g) passerine birds in the family Hirundinidae and are widespread in North America (Robertson et al 1992). Although most individuals live only two to three years in the wild, the maximum reported lifespan for the species is 12 years (Robertson and Rendell 2001). Tree Swallows constitute an ideal system to study the costs of immunosenescence because we have already demonstrated that individuals in our study population show immunosenescence in the in vivo skin swelling (Haussmann et al 2005) and the in vitro lymphocyte proliferation (Palacios et al 2007) responses to phytohemagglutinin (PHA, a common mitogen that stimulates T-lymphocytes), with immune function decreasing steadily with age in adults ranging from 1 to 8 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies demonstrating senescence in free-living organisms through measurements of age-dependent mortality, reproduction and reproductive value have been published [e.g., Gustafsson and Pärt (1990); Perdeck and Cavé (1992); Newton and Rothery (1997); Bérubé et al (1999); Møller and de Lope (1999); Espie et al (2000); Sanz and Moreno (2000); Pyle et al (2001); Robertson and Rendell (2001); Cam et al (2002); Laaksonen et al (2002); Orell and Belda (2002); Reid et al (2003)]. Several of these studies have investigated patterns of age-specific fecundity and mortality, showing how reproductive performance and survival late in life are related to early performance.…”
Section: Introductionmentioning
confidence: 99%
“…The rapidly growing literature on senescence in wild animal populations provides evidence for divergent aging patterns in female reproductive traits (48). Numerous studies of mammals, birds, and reptiles have presented simultaneous age-dependent estimates of female fecundity as well as estimates of offspring survival in mammals (11,20,24,49,50), birds (21,23,(51)(52)(53)(54), and reptiles (22,55). However, very few have formally compared the patterns of aging between these two measures.…”
Section: Discussionmentioning
confidence: 99%
“…Although observations suggest that maternal effect senescence may not proceed at the same rate as fertility senescence (12,(20)(21)(22)(23)(24), there is no evolutionary theory yet capable of explaining maternal effect senescence or its distinction from fertility senescence. Biologists have assumed that the age-related decline in selection that shapes fertility and survival generalizes to traits under the influence of IGEs, including maternal effects.…”
mentioning
confidence: 99%